Rancang Bangun Saklar Pemindah Otomatis Berpenggerak Motor Stepper Variable Reluctance Dengan Pengendali Mikrokontroler ATMega8535 - Syafarudin, Firman; Anto, Budhi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Electricity supply from PLN network is not always continually available, there could be a blackout at any time. To anticipate such outages, it is necessary to design an automatic transfer switch between the main power source and the backup power. Therefore, it is necessary to develop the automatic transfer switch equipment, where mechanically formed by cam-switch which is driven directly by variable reluctance stepper motor with microcontroller ATMega8535. Automatic mode of operation is determined by stepper motor controlled by microcontroller ATMega8535 while manual mode is done by using grip handle attached to the rotor axis of variable reluctance stepper motor. The determination electricity supply of genset and PLN conditions is determined tolerance of Â± 20% from 220 VAC standard voltage of PLN, this condition becomes the basis for moving the stepper variable reluctance motor with the angle-step position -300 for the supply of PLN (I) and +300 angle for generator (II) to move Cam-switch to supply the load. The testing design has done with the following result i.e. the variable reluctance stepper motor will rotate if fullfilled the 20% of tolerance to achieve for the uninterruptible load supply. The transition will take affect within 5 s.Keywords: Automatic transfer switch, Microcontroller ATMega8535, Variable reluctance stepper motor.